Intensive Teenage Activity Is Associated With Greater Muscle Hyperintensity on T1W Magnetic Resonance Imaging in Adults With Dysferlinopathy - Moore, Ursula; Jacobs, Marni; Fernandez-Torron, Roberto; LLauger Rossello, Jaume; Smith, Fiona E.; James, Meredith; Mayhew, Anna; Rufibach, Laura; Carlier, Pierre G.; Blamire, Andrew M.; Day, John W.; Jones, Kristi J.; et al. (Frontiers in Neurology, 2020)
Practice of sports during childhood or adolescence correlates with an earlier onset and more rapidly progressing phenotype in dysferlinopathies. To determine if this correlation relates to greater muscle pathology that persists into adulthood, we investigated the effect of exercise on the degree of muscle fatty replacement measured using muscle MRI. We reviewed pelvic, thigh and leg T1W MRI scans from 160 patients with genetically confirmed dysferlinopathy from the Jain Foundation International clinical outcomes study in dysferlinopathy. Two independent assessors used the Lamminen-Mercuri visual scale to score degree of fat replacement in each muscle. Teenage exercise information was collected from patient questionnaires. Exercise intensity for each individual was defined as no activity, minimal, moderate or intensive activity by using metabolic equivalents and patient reported frequency of sports undertaken between the ages of 10 and 18. We used ANCOVA and linear modelling to compare the mean Lamminen-Mercuri score for the pelvis, thigh and leg between exercise groups, while controlling for age at assessment and symptom duration. Intensive exercisers showed significantly greater fatty replacement in the muscles of the pelvis than moderate exercisers, but no significant differences of the thigh or leg. Within the pelvis, Psoas and Pectineus were the muscles most strongly associated with this exercise effect. In patients with a short symptom duration of less than fifteen years there was a trend towards greater fatty replacement in the muscles of the thigh. These findings define key muscles involved in the exercise-phenotype effect that has previously been observed only clinically in dysferlinopathy and support recommendations that pre-symptomatic patients should avoid very intensive exercise.